Catalysts of change: Immunotherapy's frontier in oral oncology - Shyamaladevi Babu; Madhan Krishnan (Oral Oncology Reports)
Oral cancer, which is a kind of HNSCC, presents considerable experimental difficulties because of its high rates of illness and death, often being identified at late stages. Although there have been improvements in conventional treatments such surgery, radiation, and chemotherapy, the outlook for patients is quiet unfavourable, with a five-year survival rate of around 50 %. Oral cancer has a complex origin that encompasses several variables. These include risk factors such as tobacco use, alcohol intake, and infection with human papillomavirus (HPV), as well as genetic predispositions and environmental effects. Immunotherapy has become a potential approach to treating cancer by using the immune system to specifically target cancer cells, in contrast to traditional therapies that directly assault tumours. This study examines the current immunotherapy approaches in the field of oral oncology, specifically focusing on immune checkpoint inhibitors, adoptive cell treatment, and cancer vaccines. The article explores the difficulties posed by the immunosuppressive tumour microenvironment and the need for patient-specific biomarkers to assess therapy response. The future focus is on personalized medicine and innovative therapeutic strategies, with the goal of maximizing the effectiveness of therapy and improving patient outcomes in the management of oral cancer. Ongoing research and clinical studies are essential to fully harness the promise of immunotherapy, providing fresh optimism in the battle against this intricate disease.